Project-Based Learning Training for Teachers at Madrasah Aliyah Raudhlatul Irfan, Lengkong Kulon Village - Melissa Indah Fianty; Nabila Husna Shabrina; Fahmy Rinanda Saputri (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Madrasah Aliyah Raudlatul Irfan faces challenges in the learning process as it still adopts conventional models such as lectures and assignments. Consequently, the learning experience becomes monotonous, lacking support for individual students' exploration of their abilities. Changes and increased creativity are necessary to make the learning process more engaging and to facilitate the diversity of learning abilities. The introduction of the Project-Based Learning method is expected to create a more dynamic learning environment, allowing students to develop critical thinking skills. Through projects, students have the opportunity to produce tangible evidence of their mastery of the material, while teachers have improved their skills through training. The training methods involve lectures, Q&A sessions, discussions, and demonstrations, positively impacting teachers' knowledge of Project-Based Learning. Evaluation results indicate an improvement in teachers' abilities, suggesting that this training has successfully enhanced their understanding of this innovative learning model.